Measles Metapopulation Modeling using Ideal Flow of Transportation Networks - Montalan, Jann Railey (Archīum Ateneo, 2019)
In developing countries with limited access to medical resources, infectious diseases like measles can develop rapidly within and between communities. Combination of data coming from various sources that report historical disease incidences and transportation infrastructures are valuable sources of knowledge that can assist in public health policies and initiatives surrounding disease surveillance. This study integrates population, disease incidence, and transportation network data into measles modeling. Results show that a hybrid metapopulation modeling approach using ideal flow distribution over mobility networks can yield more accurate models for measles progression. This demonstrates the feasibility of using big data in the monitoring of measles propagation.